\(Rutgonphanso:\frac{10+5}{4+5}\) Va \(\frac{2^2x9}{27x2}\)
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 7 2016

a) \(\frac{6^7}{4^3\cdot9^2}=\frac{2^7\cdot3^7}{2^6\cdot3^4}=2\cdot3^3=2\cdot27=54\)

b) \(\frac{12^3\cdot15^3}{4^3\cdot25^2\cdot9^2}=\frac{2^6\cdot3^3\cdot3^3\cdot5^3}{2^6\cdot5^4\cdot3^4}=\frac{3^2}{5}=1,8\)

c) \(\frac{2^{11}+3\cdot2^{10}}{10\cdot4^5}=\frac{2^{10}\left(2+3\right)}{2\cdot5\cdot2^{10}}=\frac{1}{2}=0,5\)

d) \(\frac{3^8\cdot2-3^6}{2\cdot17\cdot3^7}=\frac{3^6\left(3^2\cdot2-1\right)}{2\cdot17\cdot3^7}=\frac{1}{2\cdot3}=\frac{1}{6}\)

21 tháng 1 2018

Phân số nào có mẫu số nhỏ hơn thì lớn hơn.

21 tháng 1 2018

a)  \(\frac{2}{3}\) và \(\frac{1}{4}\)

Ta có:  \(\frac{2}{3}=\frac{2\times4}{3\times4}=\frac{8}{12}\)

             \(\frac{1}{4}=\frac{1\times3}{4\times3}=\frac{3}{12}\)

Vậy................

(x+1/4-1/3).(13/6-1/4)=7/46

(x+1/4-1/3).23/12=7/46

(x+1/4-1/3)=7/46:23/12

(x+1/4-1/3)=7/46.12/23

(x+1/4-1/3)=42/529

x+1/4=42/529+1/3

x+1/4=655/1587

x=655/1587-1/4

x=1033=/6348

vậy x=1033/6348

24 tháng 4 2017

1.\(\frac{5}{7}.\frac{5}{11}+\frac{5}{7}.\frac{2}{11}-\frac{5}{7}.\frac{14}{11}\)

\(=\frac{5}{7}.\left(\frac{5}{11}+\frac{2}{11}-\frac{14}{11}\right)\)

\(=\frac{5}{7}.\frac{-7}{11}=\frac{5.\left(-7\right)}{7.11}=\frac{5.\left(-1\right)}{1.11}=\frac{-5}{11}\)

\(C=\frac{-3}{7}.\frac{5}{9}+\frac{4}{9}.\frac{-3}{7}+2\frac{3}{7}\)

\(=\frac{-3}{7}.\left(\frac{5}{9}+\frac{4}{9}\right)+2\frac{3}{7}\)

\(=\frac{-3}{7}.1+2\frac{3}{7}=\frac{-3}{7}+2\frac{3}{7}=2\)

24 tháng 4 2017

câu 1:

\(\frac{5}{7}.\left(\frac{5}{11}+\frac{2}{11}-\frac{14}{11}\right)=\frac{5}{7}.-\frac{7}{11}=\frac{-5}{11}\)

1 tháng 5 2019

a, -5/6 -x = 7/12 + -1/3
⇔-10/12 - 12x/12 = 7/12 + -4/12
⇒-10 - 12x = 7 - 4
⇔-12x = 7 - 4 +10
⇔-12x = 13
⇔x = -13/12
b, x+13/-15 = 1/3
⇔-(x+13)/15 = 5/15
⇒ -x - 13 = 5
⇔-x = 5 +13
⇔-x = 18
⇔x = -18
c,-15/x-1 = -3/5
⇔-75/(x-1).5 = -3.(x-1)/5.(x-1)
⇒-75 = -3x + 3
⇔3x = 3 + 75
⇔3x = 78
⇔x = 26
d, (1/2).x + -2/5 = 1/5
⇔5x/10 + -4/10 = 1/10
⇒5x - 4 = 1
⇔5x = 1 + 4
⇔5x = 5
⇔x = 1
e, (-2/3).x + 1/5 = 1/10
⇔-20x/30 + 6/30 = 3/30
⇒-20x + 6 = 3
⇔-20x = 3 - 6
⇔-20x = -3
⇔x = 3/20
f, 4/5 - (1/2).x = 1/10
⇔8/10 - 5x/10 = 1/10
⇒8 - 5x = 1
⇔-5x = 1 - 8
⇔-5x = -7
⇔x=7/5

8 tháng 5 2019

5/2 +x=3.5

5/2+x=7/2

       x=7/2-5/2=2/2=1

-2x + 5 = 23

-2x       =23+5=28

   -x       =28:2=14

     x      = -14

x/21 = 2/7-4/3

x/21=14/21-28/21

x/21=-14/21

x=-14

5/3x-2/5x=19/10

x.(5/3-2/5)=19/10

x.19/15=19/10

x          = 19/10;19/15=19/10.15/19=3/2